Urgensi Kualitas Pelayanan Distribusi Zakat Produktif Terhadap Kepuasan Mustahiq - Sukma Mehilda; Meliyana Meliyana; Decky Hendarsyah (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2021)
Productive zakat is something that can support productivity for the economy and mustahiq life. Mustahiq satisfaction in getting productive zakat is a reflection of the success of the service. This study aims to analyze the effect of the quality of productive zakat distribution services on mustahiq satisfaction at the national zakat agency (NZA) Bengkalis district. This study was built using a quantitative descriptive method based on primary and secondary data in questionnaires, documentation, and literature studies. The total population of productive zakat mustahiq at the NZA Bengkalis regency is 327 people. Sampling used random sampling with a total sample of 77 people. Data were analyzed using simple linear regression, previously tested using validity, reliability, and normality tests. This study indicates that the quality of productive zakat distribution services has urgency in creating satisfaction for mustahiq, with evidence that the quality of productive zakat distribution services has a positive and significant effect on mustahiq satisfaction. This study contributes to NZA Bengkalis regency in improving service quality and satisfaction of productive zakat mustahiq.